Animal models for studying microglia: The first, the popular, and the new. Issue 1 (17th September 2012) - Sieger, Dirk; Peri, Francesca
Abstract Microglia, the resident phagocytes of brain, have been intensively studied since their discovery in the 1920s. There is no doubt that the possibility of culturing microglia in vitro has advanced enormously our understanding of these cells. However, as we know today, that microglia react to even small changes in the brain, it is crucial to also study these cells by preserving as much as possible their natural environment. Nowadays, advances in imaging technologies and transgenic cell labeling methods allow the direct observation of cells at work. These in vivo approaches have already changed our view on microglia by showing that these cells are active even in the healthy adult brain. As today, there is upcoming evidence that microglia can directly influence neuronal activity, understanding their roles and, in particular, their interactions with neurons is of great importance. The aim of this review is to illustrate three animal models that are currently used for microglial research and to discuss their characteristics and advantages by presenting recent achievements in microglial research. In our view the availability of different systems for studying microglia will lead to a more comprehensive understanding of their functions. © 2012 Wiley Periodicals, Inc.